THE ROLE OF VIDEOS IN ESP MATERIAL DEVELOPMENT:A THEORETICAL FRAMEWORK - Haydarova Shahrizoda (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation:  This  academic  paper  offers  a  thorough  examination  of  video integration  in  ESP  curriculum  design  by  combining  theoretical  frameworks  from applied linguistics and educational psychology with useful classroom applications. By relating Paivio's dual coding theory and CLT principles to the particular requirements of  profession-oriented  language  instruction,  the  author  builds  a  solid  theoretical framework. The work is especially beneficial since it treats opportunities and obstacles in a balanced manner, including both the practical limitations faced by educators and the  cognitive  and  motivational  advantages  of  video-based  learning.The  suggested three-phase activity structure (pre-, while-, and post-watching) provides practitioners with practical advice. The discussion of VR and AI technologies in the future places the  research  in  the  context  of  current  developments  in  education's  digital transformation.  Suggested  for  scholars  interested  in  multimedia-assisted  language learning  and  professional  communication  training,  ESP  curriculum  designers,  and language instructors in academic and professional contexts.